Niepewność i ryzyko w świetle teorii decyzji racjonalnych oraz psychologicznej teorii decyzji - Sus-Januchowska, Aleksandra (Uncertainty and risk in the light of rational decisions theory and the psychological theory of decisions, 2006)
The purpose of the article is to present the conditions of uncertainty and risk as crucial factors that have to be dealt with in making decisions in present-day organizations; these two conditions are dealt with through the prism of the theory of rational decisions and the psychological theory of decisions. This makes it possible to eliminate risk situations and makes decision-making easier.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 255-264